Perancangan Sistem Informasi Pemesanan Kontrakan Berbasis Web Di Pondok Nabila Cikarang selatan - Alfinanur Firdaus (Jurnal RESTIKOM : Riset Teknik Informatika dan Komputer, 2024)
Abstract – In its development the need for information and technology in inscreasing, causing in the old system. Problems the occur in the old system include, the process of ordering rented house by prospective occupants is still dine manually and they still write down the order list in the ledger. Where prospective rented occupants must come the location without intermediaries so that in administration error often occur in writing prospective occupants. For this reason, the author are interested in creating a system that is implemented in an online kost ordering information system application, which is an information whose development uses information technology. Ordering information system, boarding house, website, PHP, MySQL.